Characterization of expressed genes isolated from oil palm vegetative, normal and abnormal inflorescence meristems using EST approach - Lee, Yang Ping (2003)
Little is known about the function of genes expressed in oil palm vegetative meristem tissues, which are expressed during transition from vegetative to reproductive growth, and those expressed during the formation of abnormal inflorescence. This study was aimed at isolating sufficiently large numbers of expressed sequence tags (ESTs) from an oil palm vegetative meristem cDNA library so that the expression of genes in this tissue could be studied. The genes (or ESTs) that were specifically expressed in vegetative meristems at early stages of normal inflorescence meristem development, and in abnormal inflorescence meristems were isolated to study the transition from vegetative to reproductive growth and the formation of floral abnormalities from clonal palms. A random EST approach has been used to obtain vast amounts of genes from many organisms. However, the random EST approach may result in the isolation of clones that are highly repeated in proportion to their abundance in the mRNA population of the appropriate tissues. Therefore, cold-plaque screemng and suppression subtractive hybridization (SSH) techniques were employed in the EST approach to isolate as much unique transcripts as possible in this study. Based on the EST collections made from the vegetative meristem tissues, 1088 ESTs were isolated. The redundancy of the ESTs was reduced to about 18.9% where 81.1% out of 1088 oil palm vegetative meristem ESTs were unique due to the use of the cold-plaque screening approach. Classification of the putative function of ESTs provides an idea of the type of genes expressed in the vegetative meristem tissue. The expressed genes range from housekeeping genes to genes related to photosynthesis. About 44% of the ESTs were unknown and were not characterized in other species. Stage specific expressed genes were isolated from vegetative meristem, inflorescence meristem, normal and abnormal inflorescence meristem subtraction libraries. About 601 contigs were identified from these four subtraction libraries. More than 57% of the ESTs encoded unknown functions. Through the use of digital differential display calculations, the ESTs were expressed in a tissue specific manner. Reverse northern analysis confirmed that the the majority of the EST -contigs were tissue specific.This study reveals that the apical meristem devotes more cellular activity to the biosynthesis of cellular components than to photosynthesis which is predicted from the EST analysis and physiological experiments conducted on plants. This study also reveals profound changes in gene expression that are involved in the transitionfrom the vegetative meristem to an inflorescence meristem that is driven by the action of a series of genes expressed in a stage-specific manner. Significant differences in gene expression between normal and abnormal inflorescence meristems could not be detected with this EST approach. Transient changes in gene expression or epigenetic phenomenon have been proposed to explain the molecular basis of abnormal floral development.